PENGARUH E-WALLET, CREDIT CARD DAN SPENDING BEHAVIOUR TERHADAP TINGKAT KONSUMSI MAHASISWA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Aulia, Anisa; Nurlaila; Syakir, Ahmad (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of E-Wallet, Credit Cards and Spending Behavior on Student Consumption Levels at Islamic University North Sumatra Country. The studyare primary data by distributing questionnaires taken from UINSU students with a sample size of 100 people. The sampling technique used in this study is nonprobability sampling with purposive sampling type, then the data is processed using multiple linear regression analysis. The results of the study stated that E-Wallet and Spending Behavior partially has a positive and significant effect on level consumption. That is, an increase in E- Wallet and Spending Behavior will also increase consumption spending significantly. While credit cards do not have a positive effect and significantly to the level of student consumption.